A molecular dynamics study to predict the friction and wear behavior of carbon nanotube reinforced styrene-butadiene rubber. (October 2019) - Chawla, Raj; Dhawan, Manish; Sharma, Sumit
A computational method based on molecular dynamics simulation has been used to investigate the tribological behavior of carbon nanotube reinforced styrene-butadiene rubber. A three-layer molecular model in which top and bottom layers with Fe atoms and core with styrene-butadiene rubber matrices have been designed. The effect of sliding velocities from 1 m/s to 11 m/s has been studied at an applied normal loading. The properties predicted are abrasion rate and coefficient of friction. The average values of coefficient of friction and abrasion rate decrease from 0.451 to 0.328 and 21.16 to 16.5%, respectively, under sliding velocities of 1 m/s to 11 m/s. The molecular dynamics results show the decrease in coefficient of friction and abrasion rates with increasing sliding velocity.